Cd Content effects on the Performance of the MgZnO/CdZnO/ZnO Hetero structure - Kyunghan Chun, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we propose the performance improvement by inducing an increase in electric current by using a CdZnO space layer in the MgZnO/ZnOheterostructure. The polarization effect on 2DEG(two dimensional electric gas) in the MgZnO/CdZnO/ZnOheterostructure was theoretically investigated as a function of Cd content, and carrier confinement in this structure was found to be superior to that of the conventional MgZnO/ZnO HEMT(high electron mobility transistor) structure. Based on this, the performance change was observed by changing the Cd content of the space layer in the SILVACO simulation. As the Cd content increased, the electron density increased. As a result, it can be seen that the saturation drain current is proportional to the Cd content increase in the space layer.